PELATIHAN APLIKASI PLATFORM DIGITAL E-COMMERCE SEBAGAI MEDIA PEMASARAN DIGITAL PADA UMKM UP2K KELURAHAN PAALMERAH (LPPM Universitas Dinamika Bangsa, 2023)
The situation in the digital era has entered the industrial 4.0 era, where its current developments not only have an impact on technological and administrative developments but also have an impact on the economic sector. The benefits of technological developments are very huge as a turning point in changing people's lifestyles. This situation is exploited by business owners, especially MSME owners, making social media one of the media used to develop their business and business networks (Tabrani et al., 2022). For modern business people, communication and information technology networks are an alternative in managing business, both in management, and interactions between internal companies (Putra Zai et al., 2021). Marketing itself is carried out using social media and now in the form of e-commerce as a new digital media in marketing. The use of digital media in the form of e-commerce allows promotion to be carried out without limitations (ES et al., 2021). E-commerce is a good prospect for business people because it cut the operational costs. Through e-commerce sellers are not required to have physical outlets to sell their products(Ujiandari & Saputro, 2018). Keywords: Digital Marketing, E-Commerce, MSME